2007
DOI: 10.1007/s00701-007-1466-9
|View full text |Cite
|
Sign up to set email alerts
|

Side selection of pterional approach for anterior communicating artery aneurysms – surgical anatomy and strategy

Abstract: This policy provided good postoperative outcomes. However, use of skull base techniques or the interhemispheric approach, instead of the normal pterional approach, may further improve the postoperative outcome for closed A2 plane aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…This provides a better view of both A2 branches and the superiorlyprojecting aneurysm in between the branches. 26 Suzuki et al 27 approached superiorlyprojecting aneurysms from the side of the fundus projection. These authors identified a distinct group of patients with superiorly-projecting aneurysms characterized by a closed A2 plane who suffered from a higher rate of surgical complications such as vascular injury and cerebral contusion.…”
Section: Discharge Outcomes By Aneurysm Projection and Surgical Approachmentioning
confidence: 99%
“…This provides a better view of both A2 branches and the superiorlyprojecting aneurysm in between the branches. 26 Suzuki et al 27 approached superiorlyprojecting aneurysms from the side of the fundus projection. These authors identified a distinct group of patients with superiorly-projecting aneurysms characterized by a closed A2 plane who suffered from a higher rate of surgical complications such as vascular injury and cerebral contusion.…”
Section: Discharge Outcomes By Aneurysm Projection and Surgical Approachmentioning
confidence: 99%
“…There is still a need to further explore the anatomy of the anterior cerebral circulation. The results of such studies would be useful when planning surgical approaches [ 25 ], and would allow to avoid any unexpected anatomical variations during treatment of ACoA aneurysms. Such anatomical problems may include double fenestrations of the A2 segment mimicking an aneurysm neck [ 18 ] or mistaking a duplicated A1 segment for an ACoA aneurysm [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the cases of aneurysms directed posteroinferiorly and back of neck, entry into the side of the A2 located more anteriorly is recommended. Suzuki et al 12 showed the higher requirements gyrus rectus aspiration, higher incidence of residual neck remnant in closed A2 plane (p <0.0001) but no significant difference in associated vascular injury. There is significant difference in contusion was observed in patients with closed A2 plane.…”
Section: Discussionmentioning
confidence: 94%